Characteristics of Edible Film Made from Bitter Cassava Starch with Glycerol - Rumyaan, Maria; Polnaya, Febby J; Tuhumury, Helen C D (Universitas Pattimura, 2022)
The purpose of this study was to see how different glycerol concentrations affected the physical, mechanical, and barrier properties of an edible tapioca starch film. This study explored glycerol concentration using a completely randomized experimental design with four treatment levels, particularly regarding 10, 15, 20, and 25% (w/w). The tensile strength, elongation, solubility, and water vapor transmission rate of the films were all measured. Tensile strength has been 7.71 to 15.94 MPa, elongation was 13.33 to 20.00%, solubility was 15.81 to 24.81%, and water vapour transmission rate was 39.72 to 70.65 g/m2.h. Glycerol increased tensile strength whereas the decreasing elongation, solubility, and water vapour transmission rate.